Primary Prevention of Allergic Diseases: The Role of Early Exposure to Cow's Milk Formula - Mastrorilli, Carla; Santoro, Angelica; Caffarelli, Carlo (Frontiers in Pediatrics, 2020)
The burden of atopic disorders is continuously worsening worldwide, especially in childhood. Therefore, risk factors and preventive measures have been called into question. The age when infants introduce complementary foods, varies greatly according to traditional habits, clinical practice recommendations and breastfeeding duration. It is still debated the impact of early exposure to cow’s milk on the increase of allergic diseases, mainly food allergy and atopic dermatitis. Many factors may play a role in this potential link, such as genetic variation, parental atopy, infant feeding regimens. Recent evidences suggest that the early introduction of complementary foods (up to 6 months of age), including cow’s milk, could prevent the development of food allergies. So, several countries included this new approach into feeding guidelines. Our review will focus on the influence of early exposure to cow’s milk formula on the development of allergic diseases. Some trials found that cow’s milk supplementation in the first days of life could even increase the development of IgE sensitization and food allergies. Other trials did not show any efficacy on prevention of allergic disorders. Further studies are needed to understand the prospective for allergy prevention related to optimal timing of cow’s milk formula introduction.